Konteks Sosial dan Konteks Sejarah dalam Novel Senja di Jakarta Karya Mochtar Lubis: Tinjauan Sosiologi Sastra Georg Lukacs - Mayriskha, Diva; Astuty; Dewi, Liana Sinta (UPA Bahasa Universitas Tidar And HISKI Kedu, 2023)
This research is motivated by the phenomena of the social context and historical context that appear in sentences in the novel Senja di Jakarta and contain historical events that have been experienced by Indonesia. The purpose of this study is to obtain a description of the social context and historical context contained in the novel Senja di Jakarta by Mochtar Lubis. This study uses a qualitative descriptive analysis with social context and historical context research subjects. The data used are in the form of words, phrases, sentences, and discourse while the research source used is the novel Senja di Jakarta by Mochtar Lubis. The results of this study found three forms of social context, namely socio-political aspects, economic aspects, and socio-cultural aspects. There are five categories of socio-political aspects, six categories of economic aspects, and four categories of socio-cultural aspects. The historical context contains five categories which include KNIL troops, the Japanese occupation, the handover of power by the Dutch to RIS and NICA, the debate over the Irian Jaya region at the United Nations, and the betrayal of Indonesians who supported NICA.